Efisiensi Biaya Produksi terhadap Pembelian Timbangan Digital pada Proses Produksi Obat Bius Daun Ruku-ruku - Alfriado Leonard Noprian Dolok Saribu; Warsani Purnama Sari; Saribulan Tambunan; Isnaniah LKS; Linda Lores (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to assess and allocate the efficiency value obtained through the exchange of production fixed assets with substitute fixed assets. The problem is focused on Efficiency which is a measuring tool used by companies to assess how much resources are sacrificed to obtain certain results. UD PEKAN is one of the businesses engaged in the trading company which has an inefficient level of production because there are idle production assets. Therefore, it is necessary to manage production assets effectively so as to produce the maximum level of output. This type of research uses descriptive qualitative methods with qualitative and quantitative data types sourced from secondary data with documentation data collection techniques and data analysis techniques used are qualitative descriptive methods. The results showed that by replacing production assets with substitute assets, it was able to produce a level of efficiency for business actors which had an impact on production output. Where when using fixed assets the production output is 330 units/month and after using substitute assets the production output is 500 units/month. In line with the increase in production output, it also increases the total operating income of UD Pekan.